PERBANDINGAN METODE SPLIT FLUX DAN METODA DESIGN CHART DALAM PERHITUNGAN CAHAYAALAMI RUANG (DF) - Ikhwanuddin Ikhwanuddin (Universitas Negeri Yogyakarta, 2007)
Friendly environmental building design using alternative energy planning will be a trend in the future. Supplying the needs oflighting, sunlight should have been explored to be the main energy sources for lighting during the day. There are two methods to calculate the amount ofnatural light intensity in space, called DF (Daylighting Factor). Both methods use a different approach, namely Split Flux Method and Design Chart Method. Split Flux methoduse graphical approach, while Design Chart use mathematical approach. Both of methods will be tested and compare with the measurement record to ensure the most accurate calculation results.This study uses a quantitative approach. Both ofmethods will be applied in cases ofa space (the drawing room ofCivil Education and Planning Department, engineering faculty, UNY). Then the calculation results are compared with measurement results of secondary data. The data will be analysed using statistical approaches.